DAMPAK GAYA KEPEMIMPINAN, ANGGARAN BERBASIS KINERJA DAN SATUAN PENGAWASAN INTERNAL TERHADAP GOOD UNIVERSITY GOVERNANCE - Ahmad Zubaidi; Rahmad Hasibuan (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2018)
UIN Syarif Hidayatullah Jakarta since 2009 has been committed to develop becomes World Class University. The purpose is to get international recognition of UIN Syarif Hidayatullah Jakarta as one of the international quality universities. Therefor every individual and unit could to support UIN Syarif Hidayatullah Jakarta become the world class university through creation the good university governance. The variables used in this study to creation the good universitygovernance are leadership style, budget based on perforance and internal control unit.This study examines the impact of leadership style, budget based on performance andinternal control unit to Good University Governance. Sampling technique used Purposive Sampling included in non-probability sampling. Methodology used in this study is path analysis. Hypotesis testing done are directly and indirectly. The result shows for directly that leadership style has a direct effect to the good university governance. Budget based on performance does not directly affect to the good university governance and internal control unit has a direct effect to the good university governance. While indirectly the leadership style through budget based on performance has no effect to the good university governance, leadership style through internal control unit has effect to the good university governance and leadershipstyle through budget based on performance and internal control unit has affect the good university governance.